Metamict minerals : an insight into a relic crystal structure using XRD, raman spectroscopy, SAED and HRTEM - Tomašić, Nenad (Array, 2008)
Summary: Metamict minerals are characterized by an amorphization of their crystal structure due to radiation damage, and they present an interesting challenge to the mineral and material scientist. The mechanisms of the crystal structure's metamictization and thermally induced recrystallization have been found not only to be of interest for solving mineralogical and geological problems, but also for helping with practical problems, like nuclear-waste storage. This paper gives an overview of the common problems and some analytical solutions involved in obtaining information about the crystal structure of metamict minerals